An Analysis of Studentsâ€™ Grammatical Error in Writing Descriptive Texts of Second Grade Students at SMP Negeri 2 Seririt - ., M. Joko Purnomo; ., Ni Wayan Surya Mahayanti, S.Pd, M.Pd; ., Dr.Sudirman, M.L.S (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
The objectives of the research entitled â€œAn Analysis of Studentsâ€™ Grammatical Error In Writing Descriptive Text made by the Second Grade Students at SMP Negeri 2 Seriritâ€ were: 1) to find out the grammatical error which are made by students in writing descriptive text, 2) to know the cause of grammatical errors which are made by students in writing descriptive text. The subjects of this study were all students in VIIIE at SMP Negeri 2 Seririt Academic Year 2015/2016. The data were obtained from collecting studentsâ€™ writing task. The data were analyzed descriptively based on Dulay, Burt, Krashenâ€™s theory. The result of this study shows that: 1) the total amount of error made by students in their writing were 420 errors. The types of studentsâ€™ error included omission type with 228 errors (54.28%), the second is errors in misformation with 107 errors (25.47%), the third is errors in addition with 60 errors (14.28%), and the last error in misordering with 25 errors (5.95%).Kata Kunci : grammatical error, descriptive analysis, cause of studentsâ€™ errors The objectives of the research entitled â€œAn Analysis of Studentsâ€™ Grammatical Error In Writing Descriptive Text made by the Second Grade Students at SMP Negeri 2 Seriritâ€ were: 1) to find out the grammatical error which are made by students in writing descriptive text, 2) to know the cause of grammatical errors which are made by students in writing descriptive text. The subjects of this study were all students in VIIIE at SMP Negeri 2 Seririt Academic Year 2015/2016. The data were obtained from collecting studentsâ€™ writing task. The data were analyzed descriptively based on Dulay, Burt, Krashenâ€™s theory. The result of this study shows that: 1) the total amount of error made by students in their writing were 420 errors. The types of studentsâ€™ error included omission type with 228 errors (54.28%), the second is errors in misformation with 107 errors (25.47%), the third is errors in addition with 60 errors (14.28%), and the last error in misordering with 25 errors (5.95%).keyword : grammatical error, descriptive analysis, cause of studentsâ€™ errors